Al-Hafiz Abu Ahmed Al-Hassan bin Abdullah Al-Askari (293 AH-382 AH) and His Efforts in the Science of Hadith - Al-Ziadah, Haifa Mostafa; Al-Batayneh, Mishael Hani (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aimed to highlight the efforts of Imam Al-Hafiz Abu Ahmed Al-Hassan bin Abdullah Al-Askari, through his books and through scholars using his statements in the science of hadith in particular, such as Imam Ibn Hajar and Al-Sakhawi. As a contribution to introducing the prominent hadith scholars and their efforts in serving the pure Sunnah, due to the lack of an independent study that addressed it by definition and research. Methods: This study followed the inductive approach, which follows the life of Imam Al-Askari, the descriptive approach, which follows the books and writings of the imam, and the critical approach, which follows scholars use of the sayings of Imam Al-Askari. Results: One of the most important findings of the study is that Imam Al-Askari is one of the imams of knowledge in the science of hadith, and he was distinguished by the science of correction, and Al-Askari had uniqueness in this science, and he had narrations that no one else narrated. Conclusions: This study recommends working on searching for the imams of the noble hadith who served this science and were not well known among the students of hadith.